1996
DOI: 10.1126/science.274.5292.1495
|View full text |Cite
|
Sign up to set email alerts
|

The Clementine Bistatic Radar Experiment

Abstract: S>fflk+.SmSt> i 0 0,\g gN l r g t^l,-^:,g. 'X @W0-';D4:* -W u iA 27. P. de Loriol, Paleontologie Fran,aise, ou Description des Fossiles de la France, Serie 1, Animaux Invertebr6s. Terrain Jurassique (Masson, Paris, 1882-1889. 28. Because of incomplete preservation, most species have at least some missing character data. In this analysis used the species in each genus with the fewest missing characters. 29. Because unordered characters cannot be averaged, first ordinated species using principal-coordinates anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
198
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(206 citation statements)
references
References 28 publications
4
198
2
2
Order By: Relevance
“…In addition, the polar deposits of Mercury exhibit a muted CBOE, thought to be caused by admixture of silicate particles into the ice regolith [Butler et al, 1993]. As the fraction of rock fragments increases, the CBOE decreases, but both Mercury and the icy Galilean satellites show that even significant amounts of silicates cannot totally remove the CBOE effect [Nozette et al, 1996]. These relations suggest that ice deposits on the Moon could contain significant amounts of particulate contamination yet still display high-CPR values caused by CBOE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the polar deposits of Mercury exhibit a muted CBOE, thought to be caused by admixture of silicate particles into the ice regolith [Butler et al, 1993]. As the fraction of rock fragments increases, the CBOE decreases, but both Mercury and the icy Galilean satellites show that even significant amounts of silicates cannot totally remove the CBOE effect [Nozette et al, 1996]. These relations suggest that ice deposits on the Moon could contain significant amounts of particulate contamination yet still display high-CPR values caused by CBOE.…”
Section: Discussionmentioning
confidence: 99%
“…[19] High CPR on the Moon may be caused by one or both of two principal factors (1) large degrees of wavelength-scale surface roughness [e.g., Campbell, 2002Campbell, , 2012 or (2) the presence of water ice [e.g., Nozette et al, 1996Nozette et al, , 2001]. In the case of the former, geologically fresh surfaces (such as ejecta from young craters) create high degrees of surface roughness at wavelength-scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Arecibo monostatic circular polarization ratio (CPR) radar observations in the region of the lunar south pole were interpreted to possibly indicate the presence of ice deposits on the lower Earth-facing interior wall of Shackleton crater [Stacy, 1993]. Data collected by the Clementine bistatic radar experiment [Nozette et al, 1996[Nozette et al, , 1997Lichtenberg, 2000] also revealed anomalous polarization ratios in the Shackleton region, suggesting the presence of patchy, "dirty" ice deposits. Subsequently, the same Arecibo data utilized by Stacy [1993] were reported to be inconsistent with this interpretation [Stacy et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…water ice near the south pole of the Moon [Nozette et al, 1996], a more detailed analysis of these same data [Simpson and Tyler, 1999] yielded sufficient ambiguity to question their interpretation in terms of water ice. In fact, other experiments using Earth-based radar having better spatial resolution and viewing geometry indicate that the weak signature seen by Clementine originated in sunlit areas near the south pole [Stacy et al, 1997], and similar signatures were observed far from the pole where water ice cannot be stable.…”
mentioning
confidence: 99%